Mountbatten : The Official Biography - Ziegler, Philip (London Collins, 1985)
A biography of Louis, the 1st Earl Mountbatten of Burma. It examines his long and distinguished career, his wartime activites as Allied Chief of Combined Operations and his time as Viceroy and Governor General of India.
Include Index, Maps and Illustration
Keywords: Viceroys -- Great Britain. Royal Navy -- Mountbatten of Burma, Louis Mountbatten, Earl, 1900-1979